Cycling and men's health: A worldwide survey in association the Global Cycling Network. (September 2020) - Koupparis, Anthony; Mehmi, Ashley; Rava, Matteo; Kearley, Sam; Aning, Jon; Rowe, Edward; Richardson, Simon
Objectives: This study aimed to examine the association between cycling and men's health issues, including prostate cancer (CaP), erectile dysfunction (ED), chronic pelvic pain syndrome (CPPS) and lower urinary tract symptoms (LUTs). Methods: Information regarding CaP, ED, CPPS and LUTs were collected from 8074 male cyclists via a unique online men's health and cycling video produced in conjunction with the Global Cycling Network (GCN) using validated questionnaires. Logistic regression analyses were used to evaluate any relationship between cycling and men's health issues, including the effect of risk factors. Results: The GCN video received 619, 105 views, and completed data were collected on 8074 male cyclists. Of these, 0.57% had a diagnosis of CaP, 14.5% described ED, 8.82 reported symptoms of CPPS and 12.5% reported LUTs. All reported symptoms were mild, and no correlation was found between cycling and CaP or ED on statistical analyses. Conclusions: This is the largest worldwide cross-section observational study on the association between cycling and men's health. It demonstrates no negative association between cycling and CaP, ED, CPPS or LUTs. Level of evidence: Not applicable for this multicentre audit.